MXene Hollow Spheres Supported by a C–Co Exoskeleton Grow MWCNTs for Efficient Microwave Absorption - Wu, Ze; Tan, Xiuli; Wang, Jianqiao; Xing, Youqiang; Huang, Peng; Li, Bingjue; Liu, Lei (Nano-Micro Letters, 2024)
High-performance microwave absorption (MA) materials must be studied immediately since electromagnetic pollution has become a problem that cannot be disregarded. A straightforward composite material, comprising hollow MXene spheres loaded with C–Co frameworks, was prepared to develop multiwalled carbon nanotubes (MWCNTs). A high impedance and suitable morphology were guaranteed by the C–Co exoskeleton, the attenuation ability was provided by the MWCNTs endoskeleton, and the material performance was greatly enhanced by the layered core–shell structure. When the thickness was only 2.04 mm, the effective absorption bandwidth was 5.67 GHz, and the minimum reflection loss (RLmin) was − 70.70 dB. At a thickness of 1.861 mm, the sample calcined at 700 °C had a RLmin of − 63.25 dB. All samples performed well with a reduced filler ratio of 15 wt%. This paper provides a method for making lightweight core–shell composite MA materials with magnetoelectric synergy. Highlights: 1 A hollow core–shell structure was constructed with C–Co as the exoskeleton to support the MXene and multiwalled carbon nanotubes (MWCNTs) endoskeleton, with MWCNTs growing toward the center of the sphere. 2 A reflection loss of − 70.70 dB and an effective absorption bandwidth of 5.67 GHz were obtained when the thickness was only 2.04 mm. The powder filler ratio was only 15 wt%. 3 The unique hollow core–shell structure enhanced multiple reflection and scattering losses.